Pelatihan Literasi Digital Dalam Pemanfaatan Media Sosial Sebagai Media Penyuluhan Pertanian Yang Efektif Dan Efisien Bagi Petani - Gisky Andria Putra (CV. Multi Kreasi Media, 2025)
The utilization of social media in agricultural extension has emerged as a strategy deemed quite effective and efficient in disseminating information to farmers in the digital era. Social media offers easier, faster, and broader access to convey information related to agricultural technology, cultivation techniques, and the latest policies relevant to the agricultural sector. This community empowerment activity aims to encourage farmers to leverage social media to enhance their knowledge and skills. The activity employs lecture and training methods, carried out in three stages: preparation, implementation, and evaluation. The results indicate that the community service activity, aimed at encouraging farmers to utilize social media to improve their knowledge and skills, has yielded positive outcomes for farmers. The development of farmers' awareness is a crucial initial step in motivating them to use social media as a productive tool. However, challenges such as limited internet access in some areas pose a major obstacle to maximizing social media utilization. Overall, social media holds the potential to be an efficient extension tool, but it also requires support from various parties, including the government, extension organizations, and the community, to maximize its effectiveness.